OP02 Ustekinumab versus adalimumab for induction and maintenance therapy in Moderate-to-Severe Crohn's Disease: The SEAVUE study. (27th May 2021) - Irving, P M; Sands, B E; Hoops, T; Izanec, J L; Gao, L L; Gasink, C; Greenspan, A; Allez, M; Danese, S; Hanauer, S B; Jairath, V; Kuehbacher, T; et al.
Abstract: Background: We studied the efficacy and safety of ustekinumab (UST) vs adalimumab (ADA) through 1 year in biologic-naïve patients (pts) with moderate-to-severe Crohn's disease. Methods: SEAVUE was a multicenter, randomized, blinded, parallel-group, active-controlled study in adults with CD Activity Index (CDAI) scores ≥220/≤450. Biologic-naïve pts failing/intolerant to conventional therapy with any size ulcer on baseline (BL) ileocolonoscopy were eligible. Pts were randomized 1:1 to UST (⁓6mg/kg IV at BL then 90mg SC every 8 weeks [Ws]) or ADA (160/80mg SC at BL/W2, then 40mg SC every 2 Ws) per US-approved regimens (no dose modifications). Primary endpoint was clinical remission at W52 (CDAI <150). Major secondary endpoints were corticosteroid-free remission, clinical response (≥100-point CDAI decrease from BL), remission in pt-reported CDAI components (PRO-2 symptom remission: abdominal pain mean daily score ≤1 and stool frequency mean daily score ≤3), and endoscopic remission (SES-CD score ≤3/0 for pts with BL score=3) at W52 and clinical remission at W16. Results: 386 pts were randomized to UST or ADA. BL demographics and disease characteristics were balanced between groups and indicative of pts with early, moderate-to-severe CD (median CD duration, 2.58 years; CDAI, 289.5; SES-CD, 8.0). At W52, 65% of UST-treated and 61% of ADA-treated pts achieved clinical remission (Δ=4.0%; 95% CI, -5.5%, 13.5%; p=0.417). Major secondary endpoints, including endoscopic remission, were similar between groups (Table 1), as were remission rates at assessment points through W52. Some other secondary endpoints showed numerical (not statistical) differences between UST and ADA (Table 1). Key safety events are summarized in Table 2. Among UST-treated and ADA-treated pts, 34.0% and 40.5% had infections, 2.6% and 7.2% had serious adverse events (AEs) of worsening CD, and 6.3% and 11.3% had AEs that led to discontinuation (DC) of study drug, respectively. One ADA-treated pt had active pulmonary TB. Injection-site reactions associated with active treatment occurred in 1.0% of UST-treated and 10.3% of ADA-treated pts. Overall, 15.2% of UST-treated and 23.6% of ADA-treated pts DC before W52. Reasons for DC were primarily lack of efficacy (UST, 2.1% vs ADA, 5.1%), AEs (UST, 5.7% vs ADA, 10.7%), and withdrawal of consent (UST, 5.8% vs ADA, 5.1%). Time to treatment DC was longer with UST vs ADA (post hoc analysis). Conclusion: Both UST and ADA were highly effective in this population of biologic-naïve pts. Rates of clinical remission at W52 were not statistically significantly different between treatment groups. DC rates were numerically lower for UST. Safety results were consistent with prior experience for both treatments.